Comb-Assisted Cavity Ring Down Spectroscopy of 17O enriched water between 6667 and 7443 cm−1. (February 2018) - Mikhailenko, S.N.; Mondelain, D.; Karlovets, E.V.; Kassi, S.; Campargue, A.
Highlights: The CRDS spectrum of 17 O enriched water vapour is recorded between 6667 and 7443 cm −1 . 9144 water lines were assigned to 9988 transitions of six isotopologues. 2300 new H2 17 O transitions were assigned and 64 new energy levels were derived. The uncertainty on the center of unblended lines is on the order of 10 −4 cm −1 . Some deficiencies of the HITRAN2016 line list of water vapor are evidenced. Abstract: The room temperature absorption spectrum of water vapour highly enriched in 17 O is studied by Comb Assisted-Cavity Ring Down Spectroscopy (CA-CRDS) near 1.4 µm. The investigated spectral region (6667–7443 cm −1 ) is a strong absorbing region corresponding to the first hexade of interacting vibrational states. As a consequence of the high sensitivity of the recordings (Noise Equivalent Absorption, αmin ∼ 10 −10 cm −1 ), a series of spectra could be recorded at very low pressure (less than 0.1 Torr) allowing for accurate determination of line centres and the spectral resolution of highly blended multiplets. For instance, 85 lines of the main isotopologue located near much stronger lines are measured for the first time. The assignments were performed using known experimental energy levels as well as calculated line lists based on the results of Schwenke and Partridge. Overall, the experimental list includes 9144 water lines which were assigned to 9988 transitions of six isotopologues (H2 16 O, H2 17 O, H2 18 O, HD 16 O, HD 17 O and HD 18 O). Their intensities span six orders of magnitude from 10 −27 to 10 −21 cm/molecule at 296 K. Most of the new results concern the H2 17 O isotopologue: more than 2300 new lines were measured, 64 new levels were determined and seven levels were corrected. In the case of HD 17 O, 152 new transitions were assigned and ten levels were newly determined. The center values of non-blended lines are reported with an accuracy better than 3 MHz (10 −4 cm −1 ) which represents an improvement compared to previous determinations. The comparison to the water vapor line list provided by the recently released 2016 version of the HITRAN database reveals a number of issues.